Vigorous physical activity and weight status in school-aged children: a cross-sectional study - Yu, Weijun; Xu, Shuanglu; Dai, Xiaojie; Fan, Huiying (Frontiers in Public Health, 2024)
Aim To explore the association between VPA and weight status in adolescents. Methods The 2017/2018 Health Behavior in School-aged Children survey (HBSC) targeted children and adolescents aged 11, 13 and 15. A systematic multistage stratified cluster randomized sampling method was used in each participating country. The 2017/2018 survey enrolled over 240,951 adolescents across 45 countries and regions. Frequency of VPA, weight status and confounding factors were collected using a self-reported questionnaire. Results Compared to daily VPA, less frequent VPA was linked to higher odds of obesity. For example, those who participating in VPA for 4–6 times a week (OR = 1.10, 95% CI = 1.06–1.13), 2–3 times a week (OR = 1.21, 95% CI = 1.17–1.25), or once a week (OR = 1.21, 95% CI = 1.16–1.25) all have higher odds of abnormal weight status. For boys, the frequency of 4–6 times a week (OR = 1.09, 95% CI = 1.04–1.13), 2–3 times a week (OR = 1.22, 95% CI = 1.17–1.27), or once a week (OR = 1.25, 95% CI = 1.19–1.32) were associated with higher odds of abnormal weight status. For girls, those who participating in VPA 4–6 times a week (OR = 1.11, 95% CI = 1.06–1.16), 2–3 times a week (OR = 1.20, 95% CI = 1.14–1.25), or once a week (OR = 1.17, 95% CI = 1.11–1.23) all have higher odds of abnormal weight status (i.e., overweight or obesity). Conclusion This population-based study suggests that infrequent VPA participation is associated with unhealthy weight status in adolescents compared to their physically active counterparts. Additionally, this association remains consistent in both boys and girls.